Pancasila as the Foundation of Value Development in Science - Bambang Yuniarto; Budi Akung Cholid; Nazmi Khalifatan Ya’afi.ni; Nurussaadah Nurussaadah; Adelisah Adelisah (International Journal of Social Science and Community Service, 2025)
This research aims to explore the role of Pancasila as a basic framework in the development of scientific values in Indonesia. The research method used is a qualitative approach through literature study and descriptive survey. The research involved analyzing the perceptions of scientists, educators, and students towards the influence of Pancasila values in their scientific practices. The results showed that the majority of respondents (75%) recognized the importance of integrating Pancasila values, such as ethical responsibility, social justice, and national identity, into scientific activities. As many as 80% of respondents felt that these values promote transparency and integrity in research. However, the study also identified significant challenges, such as a lack of institutional support and pressure to meet global standards that often overlook local contexts. The conclusion of this study confirms that Pancasila can be a strong ethical foundation in scientific practice, encouraging scientists to consider the social and cultural impacts of their research. Implications of this study include the need for policies that support the integration of Pancasila values in education and scientific research to create a research ecosystem that is more inclusive, ethical, and relevant to the needs of Indonesian society.